As guardiãs dos cerrados e suas narrativas de lutas e resistências - Simony Lopes da Silva Reis (Confins)
The Brazilian cerrados suffer with increasing territorial intensity and world producers on these homogeneous spaces, agribusiness and business creation on these homogeneous spaces, agribusiness and breeders at the highest intensity of commodities. In contrast to this narrative, Cerradeiras women elaborate strategies of struggle to endorse and strengthen other narratives about the cerrados. Ecofeminist narratives based on diversity, otherness and horizontality of the territorialities of the peoples of the cerrados. Therefore, this work seeks to highlight the female writings about the Bahian cerrados, highlighting the fundamental role of women as guardians of the cerrados.